Between the sacred and politics: the Visigothic State in the Councils of Toledo - Lopes, Maria Eduarda de Sousa; Charrone, João Paulo (Romanitas - Revista de Estudos Grecolatinos, 2026)
This study aims to present a historically grounded concept of the State that aligns with the socio-political formations of the Early Medieval Western kingdoms, while analyzing the complex theoretical framework of domination and dependency relations within Visigothic society. The primary sources used are the Acts of the Councils of Toledo, published in Latin-Spanish by Investigaciones Científicas, supplemented by a variety of scholarly works examining the political thought and social structure of the Visigothic Kingdom.
Keywords: Medieval State; Visigothic Kingdom; Councils